Techniques for reading comprehension - Rodallega Campo, Martha Cecilia; Alulima Alulima , Lidya Dolores (SATHIRI, 2024)
Reading comprehension is a cognitive process oriented to the interaction between the reader and the text, a skill that regularly takes place within the educational environment. Within this context, a purpose is generated to identify reading comprehension techniques relevant to educational contexts. This exploration was developed through a bibliographic review, research that culminates with a qualitative approach of exploratory-descriptive scope with a non-experimental design. With results that are evidenced in Table 1, with internal factors where there are equal criteria focused on the school and a numerable percentage in external factors that are related to the techniques to be implemented in the classroom for the benefit of reading comprehension. In short, the techniques related to reading comprehension are diverse and can be used in different contexts within the educational environment, regardless of the area of knowledge, age group or level of education.
Keywords: Reading Comprehension; Education; Reading; Techniques